COMPARISON OF ROAD TRAFFIC ACCIDENT DEATH BETWEEN ALMATY CITY AND NUR-SULTAN - Nayab, Ahamad Hamed; Anwari, Mohammad Taqi (Interdisciplinary Approaches to Medicine, 2021)
Deaths caused by road accidents are a big concern all over the world and every year near 1.3 million people die due to it.This study aimed to find the mortality rate due to RTA (Road Traffic Accident) based on gender, city, year and comparing the rate of RTAD (Road traffic accident death) to total death and deaths due to external cause from 2010 to 2019 in two major cities of Kazakhstan, Almaty city and Nur Sultan. And also to find the cause of death in forensic medicine to what degree of the injury whether the head or other part of the body is more to be the cause of death.The study design was quantitative cross-sectional. The data were obtained from the demographic yearbook of Kazakhstan for 10 years. For analyzing the data, the SPSS version 22 was used.The total number of deaths due to RTA in two major cities of Kazakhstan, Almaty and Nur sultan, from 2010 to 2019 was 2632. Among them 1732 (68.4%) were male, and 833 (31.6%) were female. In Almaty city, it was 1805 (68.6%) and in Nur Sultan city it was 827 (31.4%). The high rate among males was in between the age group of 30 – 39 while for the female it is 50 – 59 According to sex distribution males are more prone to have road traffic accident deaths comparing to females. The cause of death due to RTAD are around 65% in the head and 15% in the chest. The fracture of the femur bone is more prevalent among males and the fracture of humerus bone was more prevalent among females.This rate study of road traffic accident deaths might contribute to reducing the numbers of deaths due to RTA in Kazakhstan.